The feasting table as the gateway to hell on the early modern stage and page - Seymour, L (Wiley, 2019)
When banquets are performed on the early modern stage, devils can be seen beside the eaters. This is notably the case when grace has not been said properly before the meal. This article focuses on a group of four texts: Thomas Dekker's If This Be Not a Good Play, The Devil Is In It (1611), Thomas Heywood and Richard Brome's The Late Lancashire Witches (1634), William Winstanley's The Essex Champion (1690?), and Christopher Marlowe's Dr Faustus (c.1592). These texts contain particularly striking examples of an early modern anxiety about the importance of saying grace and eating piously rather than greedily for maintaining hierarchies within the state and the household. They also show the ways in which debates about the Eucharist underlie, and can be mapped on to, representations of saying grace. The article demonstrates that the theatre makes visible early modern concerns about souls imperilled and household hierarchies destabilised by improper eating practices.